Penggunaaan tepung gaplek dan jus tape singkong sebagai starter untuk meningkatkan kualitas fisik dan pH silase - Syifa Nurjannah; Nilawati Widjaja; Sari Suryanah; Hilman Permana; Ade Irma Fitriyani (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Corn straw is an alternative substitute for forage for animal feed in the dry season, but corn straw has low quality and short shelf life. The provision of starters is carried out to preserve and improve the quality of corn straw silage. This study aims to determine the effect of using various levels of cassava flour and cassava tape juice as starters on the physical quality and pH of corn straw silage. This study was carried out with a Complete Random Design (RAL), consisting of 20 experimental units with 4 treatments and 5 replicates, namely P1: corn straw without cassava tape juice and cassava flour as control, P2: corn straw + 1.5% cassava tape juice and 1.5% cassava flour, P3: corn straw + 3% cassava tape juice and 3% cassava flour, P4: corn straw + 4.5% cassava tape juice and 4.5% cassava flour. The data were analyzed using Analysis of Varians (ANOVA) and continued with Duncan's Multiple Ranges Test (DMRT). The data from the study showed that the use of cassava flour and cassava tape juice had a real effect (p<0.05) on physical quality which included color, aroma, texture, smell, and the presence of mold as well as the pH of corn straw silage.  It can be concluded that the using corn straw with 1.5% cassava flour and 1.5% cassava tape juice produced the best silage quality and pH compared to other treatments in terms of good physical quality, the lowest pH achievement, and the absence of mold.